Aesthetics of 1950s and 1960s interiors presented in Polish comedy films from that period - Wojciechowska-Kucięba, Joanna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
This article is an attempt at outlining key aesthetic standards of interior design of the 1950s and 1960s on the basis of examples exhibited in the Polish and foreign romantic comedies of that time. Some distinguishing features of 1960s Polish aesthetics were the characteristic abstract language, organic form, asymmetry, diagonal lines, arrangements based on “A” and “X” letter outlines and lively colours. Furniture design used new materials mostly plywood and plastics such as polyvinyl chloride and epoxy resins. The 1960s, called “small stabilization” by design historians, were slightly different. Shops offered a variety of new products designed by Polish creators – such as furniture, home appliances, tools and machines. New Polish industrial design of 1960s is represented by the RAMONA and EWA radios and the BAMBINO record player, whereas sectional furniture – especially SYSTEM MK designed by Bogusława and Czesław Kowalski, better known as “the Kowalskis’ furniture” – became the icon of the decade. Polish and foreign romantic comedies from 1950s and 1960s are an excellent iconographic source of information on how interior design changed in the second half of the 20th century, and specifically on how living space was organized and adapted for private and public purposes. In Poland, attempts were made to use all the “design innovations” coming from the west, however, the immutably closed Polish borders prevented them from spreading freely. We had to use local designers. In the 2nd half of the twentieth century, a period which Prof Irena Huml called “the invasion of modernity” started. The doctrine of socialist realism was rejected and the focus was on modernity. Innovation became the most desirable feature of a work of art, and modernity the most important concept.